Upaya dalam Pelindungan Hukum bagi Tenaga Kesehatan yang Melakukan Pelanggaran Ringan - Hotmaria Hertawaty Sijabat (CV. ADIBA AISHA AMIRA, 2024)
Legal protection for health workers who commit minor offences is an important aspect in maintaining the quality and safety of health services. Health workers are often put in challenging and complex situations, which increase the risk of minor offences. Adequate and clear legal protections are needed to give health workers a sense of security in performing their duties, as well as to ensure that the legal consequences faced are not excessive. Key points in this include the provision of legal counsel, fair and transparent internal policies, and ongoing education and training regarding professional ethics and applicable regulations. In addition, it is important to build a supportive work culture, where health workers feel safe to report misconduct without fear of disproportionate reactions. With these measures, it is expected that the quality of medical services will improve and the welfare of health workers will be more secure.